Conscientiousness, procrastination and perfectionism - Juliano, Cheryl A. (2006)
Conscientiousness and its relationship with procrastination (self-reported and behavioral procrastination) and perfectionism (personal standards, organization and overall perfectionism) were examined in order to establish its validity. Data were collected from 38 fourth year high school students who responded to three questionnaires: Disiplinado Scale of the Panukat ng mga Katangian ng Personalidad; Lay's General Procastination Scale; and the Frost Multidimensional Perfectionism Scales. Correlation analysis showed that PKP Conscientiousness was negatively related to self-reported procrastination and positively related to organization. Furthermore, conscientiousness was not related to behavioral procrastination, personal standards, and overall perfectionism.
Keywords: High school student attitudes; Behavioral assessment; Conscience; Procrastination; Perfectionism (Personality trait)